Big-needle knit afghans - Stauffer, Jeanne; House of White Birches; Stauffer, Jeanne; House of White Birches (Berne, IN : House of White Birches, 2004)
Each afghan in this book is knit on needles size 10 1/2 and up. Some are made with bulky yarns and others use multiple strands of worsted or sport-weight yarn. Includes baby afghans, afghans with texture and 3-D flowers, and gorgeous afghans with cables.
Keywords: Afghans (Coverlets); Knitting -- Patterns